Passive Acoustic Monitoring Reveals Spatio-Temporal Distributions of Antarctic and Pygmy Blue Whales Around Central New Zealand - Warren, Victoria E.; Širović, Ana; McPherson, Craig; Goetz, Kimberly T.; Radford, Craig A.; Constantine, Rochelle (Frontiers in Marine Science, 2021)
Effective management of wild animal populations relies on an understanding of their spatio-temporal distributions. Passive acoustic monitoring (PAM) is a non-invasive method to investigate the distribution of free-ranging species that reliably produce sound. Critically endangered Antarctic blue whales (Balaenoptera musculus intermedia) (ABWs) co-occur with pygmy blue whales (B. m. brevicauda) (PBWs) around New Zealand. Nationally, both are listed as ‘data deficient’ due to difficulties in access and visual sub-species identification. PAM was used to investigate the distributions of blue whales via sub-species specific song detections in central New Zealand. Propagation models, incorporating ambient noise data, enabled the comparison of detections among recording locations in different marine environments. ABW detections peaked during austral winter and spring, indicating that New Zealand, and the South Taranaki Bight (STB) in particular, is a migratory corridor for ABWs. Some ABW calls were also detected during the breeding season (September and October). PBW calls were highly concentrated in the STB, particularly between March and May, suggesting that an aggregation of PBWs may occur here. Therefore, the STB is of great importance for both sub-species of blue whale. PBW detections were absent from the STB during parts of austral spring, but PBWs were detected at east coast locations during this time. Detection area models were valuable when interpreting and comparing detections among recording locations. The results provide sub-species specific information required for management of critically endangered ABWs and highlight the relative importance of central New Zealand for both sub-species of blue whale.